The Association Between Passive Smoke Exposure and the Incidence of Pneumonia in Children Under Five: A Systematic Review - Khujaefah; Ilham Prayogo (International Medical Journal Corp. Ltd, 2025)
Introduction: Pneumonia remains the foremost infectious cause of mortality in children under five years of age globally, disproportionately affecting those in low- and middle-income countries. Concurrently, a substantial proportion of this vulnerable population is involuntarily exposed to passive tobacco smoke, a known and modifiable risk factor for respiratory illness. This systematic review aims to synthesize and critically evaluate the contemporary evidence on the association between passive smoke exposure and the incidence and severity of pneumonia in young children. Methods: This review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A comprehensive search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library was performed to identify observational studies (cohort, case-control, cross-sectional) that quantified the risk of pneumonia or lower respiratory tract infection (LRTI) associated with passive smoke exposure in children under five. Two independent reviewers performed study selection, data extraction, and quality appraisal using the Cochrane Risk of Bias in Non-randomized Studies – of Interventions (ROBINS-I) tool. Results: Seventeen primary observational studies and several supporting meta-analyses met the inclusion criteria. The synthesized evidence demonstrates a consistent and statistically significant association between passive smoke exposure and an increased risk of pneumonia. Pooled data from prior meta-analyses indicate that smoking by any household member increases the risk of LRTI by approximately 54% (OR=1.54, 95% CI 1.40–1.69). Postnatal maternal smoking was identified as the most potent risk factor (OR=1.58, 95% CI 1.45–1.73), conferring a greater risk than paternal smoking alone (OR=1.22, 95% CI 1.10–1.35). A clear dose-response relationship was observed, with risk escalating with the number of smokers in the household and the quantity of cigarettes smoked. Furthermore, exposure was linked to increased disease severity, including a higher likelihood of hospitalization (aOR 1.55, 95% CI 1.25–1.92), longer hospital stays, and increased need for intensive care (aOR 1.44, 95% CI 1.05–1.96). Discussion: The strength, consistency, and dose-response nature of the observed association across diverse global populations, combined with established biological mechanisms, strongly support a causal relationship. Passive smoke exposure impairs lung development in utero, disrupts postnatal mucociliary clearance, suppresses local immune function, and increases nasopharyngeal carriage of key respiratory pathogens. The heightened risk associated with maternal smoking is likely attributable to the combined effects of prenatal exposure on lung architecture and intense postnatal proximity. Conclusion: There is robust and conclusive evidence that passive smoke exposure is a major, preventable cause of pneumonia incidence and severity in children under five. These findings mandate urgent public health action, including strengthening smoke-free legislation and integrating smoking cessation support into routine maternal and child health services to protect this vulnerable population.